THE DISCURSIVE RE-CODIFICATION OF GENDER PARADIGMS IN GLOBAL DIGITAL DISCOURSE - Zaripboyeva Nafosat Maratovna (International Journal of Literature and Language Studies, 2026)
This article explores the cross-cultural pragmatic mechanisms through which traditional gender stereotypes are systematically deconstructed and re-codified within English, Russian, and Uzbek digital media spaces. Drawing on John Searle’s taxonomy of speech acts and Stephen Levinson’s generalized conversational implicature, the study evaluates how user-generated micro-texts operate as active instruments of social change. Rather than treating these digital streams as passive reflections of culture, this analysis fosters a deeper understanding of how extreme textual density accelerates shifts in collective gender roles through strategically coordinated macro-structures.